The Relationship between Air-Mass Trajectories and the Abundance of Dust-Borne Prokaryotes at the SE Mediterranean Sea - Eyal Rahav; Natalia Belkin; Adina Paytan; Barak Herut (Atmosphere, 2019)
Airborne prokaryotes are transported along with dust/aerosols, yet very little attention is given to their temporal variability above the oceans and the factors that govern their abundance. We analyzed the abundance of autotrophic (cyanobacteria) and heterotopic airborne microbes in 34 sampling events between 2015−2018 at a coastal site in the SE Mediterranean Sea. We show that airborne autotrophic (0.2−7.6 cells × 103 m−3) and heterotrophic (0.2−30.6 cells × 103 m−3) abundances were affected by the origin and air mass trajectory, and the concentration of dust/aerosols in the air, while seasonality was not coherent. The averaged ratio between heterotrophic and autotrophic prokaryotes in marine-dominated trajectories was ~1.7 ± 0.6, significantly lower than for terrestrial routes (6.8 ± 6.1). Airborne prokaryotic abundances were linearly and positively correlated to the concentrations of total aerosol, while negatively correlated with the aerosol’s anthropogenic fraction (using Pb/Al or Cu/Al ratios as proxies). While aerosols may play a major role in dispersing terrestrial and marine airborne microbes in the SE Mediterranean Sea, the mechanisms involved in the dispersal and diversity of airborne microorganisms remain to be studied and should include standardization in collection and analysis protocols.